Eigenvalues of Cayley Graphs - Liu, Xiaogang; Zhou, Sanming (The Electronic journal of combinatorics, 2022)
We survey some of the known results on eigenvalues of Cayley graphs and their applications, together with related results on eigenvalues of Cayley digraphs and generalizations of Cayley graphs.